The Influence of Leadership, Motivation, Discipline and Work Environment on the Performance of Employees at Batang Laping (BALAP) PTPNIV - Nasution, Nurhadida; Yanti, Mariana Eva (Journal of Agriculture, 2023)
This study aims to (1) determine the condition of leadership, motivation, discipline, work environment on employee performance at PT Perkebunan Nusantara IV Balap Estate. (2) Knowing the concept of leadership, motivation, discipline, work environment on employee performance at PT Perkebunan Nusantara IV Balap Estate. (3) Knowing the effect of leadership, motivation, discipline, work environment on employee performance at PT Perkebunan Nusantara IV Balap Estate. Report collection was carried out at PT Perkebunan Nusantara IV Balap Estate, Mandailing Natal District. The population is all employees of the Balap Estate with a total of 300 people. Withdrawal of samples using purposive sampling technique so that the total sample is 85 people. Data analysis used the Likert Scale method and the SmartPLS method.